Pelaksanaan Model Pembelajaran Sentra Untuk Anak Berkebutuhan Khusus - Munarmi, Ineke; Damri, Damri (Jurnal Penelitian Pendidikan Khusus, 2023)
This study aims to describe the process of implementing the learning center model for Children with Special Needs at schools providing inclusive education in Kindergarten Telkom Padang. According to the theory described, there are seven centers in PAUD schools, namely: beam centers, worship centers, role playing centers, preparation centers, music centers, arts and creativity centers, and nature centers. The research method that the researcher uses is descriptive qualitative by describing phenomena and events as they are. The subjects in the study were classroom teachers who had children with special needs in their class. While the research informants were the principal and all center teachers other than those with special needs children in their class. Data were collected through observation, interviews and documentation studies which were then analyzed, presented and conclusions drawn from these data. Based on the data and research results obtained from the research conducted, the implementation of the learning center model at schools providing inclusive education will be effective for early childhood children with special needs.